Gaya Bahasa Teras Berita Covid-19 pada Saluran Youtube CNN Indonesia - Yusandra, Titiek fujita; Helda, Trisna (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2020)
This study aimed to describe the style of language on the terrace of news about Covid-19 as seen from the terrace / stylistic lead's writing style. A good news writer tries hard not to want to be too mechanistic. Rigid lead writing will feel tedious and unattractive. News that gives the possibility to treat as a feature are beautified, enlivened, even made like creative writings so that they are attractive to the audience. The approach used was descriptive qualitative. This research's data was the core/intro/lead of Covid-19 news that contains a stylistic style. Data obtained from the CNN Indonesia YouTube social media channel was present around the time of the research, namely starting from March to October. The data collection method used was the observation method with record and note techniques. Data were selected, classified, identified, and then described based on the stylistic lead theory. Nine stylistic terraces obtained from thirteen kinds of stylistic core used in disclosing Covid-19 news leads as the results of the study, namely: (1) punching leads, (2) descriptive leads, (3) contrast leads, (4) questioning leads, (5) quote leads, (6) cumulative curiosity leads, (7) sequential leads, (8) parody leads, and (9) greeting leads.